2016
DOI: 10.1063/1.4964091
|View full text |Cite
|
Sign up to set email alerts
|

The excited-state structure, vibrations, lifetimes, and nonradiative dynamics of jet-cooled 1-methylcytosine

Abstract: We have investigated the S0 → S1 UV vibronic spectrum and time-resolved S1 state dynamics of jet-cooled amino-keto 1-methylcytosine (1MCyt) using two-color resonant two-photon ionization, UV/UV holeburning and depletion spectroscopies, as well as nanosecond and picosecond time-resolved pump/delayed ionization measurements. The experimental study is complemented with spin-component-scaled second-order coupled-cluster and multistate complete active space second order perturbation ab initio calculations. Above th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 68 publications
5
24
0
Order By: Relevance
“…Nanosecond laser two-color resonant two-photon ionization (2C-R2PI) spectra of the amino-keto tautomers of (a) 6-methylCyt, (b) 1-ethylCyt, , (c) Cyt (with atom numbering), (d) 1-methylCyt, , (e) 5-methylCyt, (f) 5-fluoroCyt, (g) 5,6-trimethyleneCyt, and (g) 1-methyl-5,6-trimethyleneCyt. Ionization wavelength: 226 nm for panels c and e, 223 nm for panel d, 220 nm for panels a and b, and 245 nm for panels f–h.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosecond laser two-color resonant two-photon ionization (2C-R2PI) spectra of the amino-keto tautomers of (a) 6-methylCyt, (b) 1-ethylCyt, , (c) Cyt (with atom numbering), (d) 1-methylCyt, , (e) 5-methylCyt, (f) 5-fluoroCyt, (g) 5,6-trimethyleneCyt, and (g) 1-methyl-5,6-trimethyleneCyt. Ionization wavelength: 226 nm for panels c and e, 223 nm for panel d, 220 nm for panels a and b, and 245 nm for panels f–h.…”
mentioning
confidence: 99%
“…The spectroscopic and lifetime measurements of cold gas-phase cytosines are advantageous because they can be conducted tautomer-specifically, ,, and the molecules are excited in a narrow energy window of ∼10 cm –1 (1.2 meV). Our much better energy resolution allows direct comparison to high-level excited-state calculations of the decay paths, and the nanosecond (ns) laser spectra with highly resolved vibronic bands yield detailed information on the structure of the optically excited S 1 ( ππ *) state, the vibrations that are excited upon S 0 → S 1 excitation, and the direction of the transition dipole moments. …”
mentioning
confidence: 99%
“…At λ pump $ 290 nm, the photon energy is close to the origin of enol-5mCy with a minimal excitation probability due to poor Franck-Condon (FC) factors. [17,18] With λ pump < 290 nm, the 1 ππ* state of both enol and imino forms should become energetically accessible. Table 3 also lists the oscillator strengths calculated at the PBE0/ def2-TVZP level.…”
Section: F I G U R E 5 Energy Level Diagrammentioning
confidence: 99%
“…The fastest decay component (τ 1 ) is present in transients measured at all λ pump 's and exhibits a robust time constant of about 0.25 ps. Because it has been shown that the excited-state deactivation rates of Cy derivatives are very sensitive to the excess energy above the origin, [9,12,[15][16][17]26] this rather independence of the τ 1 component on λ pump over a large energy range ($0.7 eV) suggests that it is not likely to be due to an excited-state population decay of 5mCy tautomers. Indeed, its time scale suggests that it is more likely to be due to an initial intramolecular vibrational-energy redistribution (IVR) occurring in excited 5mCy tautomers.…”
Section: The Assignmentsmentioning
confidence: 99%
See 1 more Smart Citation